2015
DOI: 10.1021/acs.jced.5b00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Na, Ca, Mg, and Al Chloride Salts on Dissolution and Phase Stability of Calcium Sulfate Dihydrate in Aqueous Solutions at 278.15 K to 308.15 K

Abstract: Dissolution trend and solubility data of calcium sulfate dihydrate (CaSO 4 ·2H 2 O gypsum) in aqueous Na, Ca, Mg, and Al chloride salt solutions have been studied at 278.15 K to 308.15 K. The concentration ranges were up to 4.5 mol·L −1 for NaCl, 3.0 mol·L −1 for MgCl 2 , 2.0 mol·L −1 for CaCl 2 , and 1.6 mol·L −1 for AlCl 3 , respectively. Measurement results show that except for CaCl 2 , the other three salts allow the solubility of gypsum to rise a lot first and then descend smoothly after attaining the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…Regardless of the variation in temperature, the measured maximum amount of the solubility is approximately 0.7 g/L. These findings are quite similar to those noticed in other previous relevant studies [20]. For all the examined concentrations, the solubility of Phosphogypsum is positively associated with temperature values; this implies that as the temperature increases the Phosphogypsum solubility increases in aqueous NaCl solutions too.…”
Section: A Effect Of Nacl Concentration and Temperature On The Solubsupporting
confidence: 90%
See 1 more Smart Citation
“…Regardless of the variation in temperature, the measured maximum amount of the solubility is approximately 0.7 g/L. These findings are quite similar to those noticed in other previous relevant studies [20]. For all the examined concentrations, the solubility of Phosphogypsum is positively associated with temperature values; this implies that as the temperature increases the Phosphogypsum solubility increases in aqueous NaCl solutions too.…”
Section: A Effect Of Nacl Concentration and Temperature On The Solubsupporting
confidence: 90%
“…The paper presents the results of the dissolution characteristics of heavy and radioactive elements from PG, which is a by-product result from the industry of phosphate fertilizers. Leachability of heavy and radioactive elements in deionized water that has been inspected under various states of leaching, including solid/liquid ratio (10,20 and 50 /1g/L) and temperatures (25, 45 and 85 °C), with constant other parameters such as string speed (300 rpm) and contact time (60 minutes). For the most analysis elements, the progressive release of the metals, in addition to the major elements reflects high mobility.…”
mentioning
confidence: 99%
“…We use the EDB for solubility data after 1965; however, we found that the EDB does not include many solubility data sets in the CaSO 4 system. As a result, we included additional solubility data in the CaSO 4 system from the sources listed in Arslan and Dutt, as well as including several other sources. Similarly, for the MgSO 4 system we include solubility data sets for meridianiite and the freezing-point depression of ice. , In the Mg–Cl–SO 4 system, which is important because this system contains solubility measurements for various MgSO 4 hydrates, we include several additional sources from Bousmina et al, Bursa and Stanisz-Lewicka, and Li et al . We also include multicomponent solubility data in the five and six component systems from Wetian et al, Goroshchenko et al, Perova, , Huang et al, and Zuomei et al, , which give solubility measurements for polyhalite and other mixed sulfate minerals at several temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…The nucleation and growth rates of the DH crystal are determined by its equilibrium solubility (C*), and according to several previous reports, [44][45][46][47] the value of C* in this system can be measured by a seeded growth equilibration method and the data are displayed in Table 3. The C* value of saturated gypsum solution can be increased effectively by the introduction of Cu 2+ , and as the concentration of Cu 2+ increases, the C* value is increased gradually.…”
Section: Resultsmentioning
confidence: 99%